Association of the cardiometabolic index with sarcopenia among U.S. adults: NHANES 2011–2018 findings - Qing Zhao; Yue Xu; Xiaotian Chen (PLoS ONE, 2025)
Background The cardiometabolic index (CMI), initially devised as a diagnostic tool for diabetes mellitus, has evolved into a composite biomarker for evaluating metabolic syndrome and cardiovascular disease risk. In order to shed light on any possible interactions between sarcopenia and CMI, this study will look at the relationship between the two. Methods and results Data from the 2011–2018 National Health and Nutrition Examination Survey (NHANES) were analyzed to investigate the possible link between sarcopenia and CMI. Among 3,185 eligible participants, the weighted prevalence of sarcopenia was 7.84%. A significant positive association emerged between CMI and sarcopenia risk, with each unit increase in CMI was linked with a 12% greater risk of sarcopenia in the fully adjusted model (OR: 1.12; 95% CI: 1.01–1.26). Moreover, dose-response relationships were evident across CMI tertiles (P for trend < 0.05). Subgroup analyses and interaction tests indicated that the positive correlation between CMI and the risk of sarcopenia differs significantly across subgroups defined by education level, sedentary time and CVD status (all P for interaction < 0.05). Conclusions Our findings demonstrate a robust association between elevated CMI levels and increased sarcopenia risk, suggesting CMI’s potential utility as a clinical biomarker for sarcopenia risk surveillance. To confirm these results and demonstrate causality, more research is required.